2004
DOI: 10.4049/jimmunol.173.1.531
|View full text |Cite
|
Sign up to set email alerts
|

TLR3-, TLR7-, and TLR9-Mediated Production of Proinflammatory Cytokines and Chemokines from Murine Connective Tissue Type Skin-Derived Mast Cells but Not from Bone Marrow-Derived Mast Cells

Abstract: Recent studies have revealed that murine bone marrow-derived cultured mast cells (BMMC), which are phenotypically immature mast cells, express functional TLR2 and TLR4 that recognize distinct pathogen-associated molecules. However, it remains relatively uncertain whether mast cells express other TLR. We recently established a method to obtain large numbers of murine fetal skin-derived cultured mast cells (FSMC); these cells exhibit important features of connective tissue type mast cells. Working with FSMC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
224
3
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(248 citation statements)
references
References 82 publications
17
224
3
4
Order By: Relevance
“…[2][3][4][5] An alternative approach, irrespective of the immunization route, is to enhance T-cell attraction to the tumor site through the local application of selected chemokines 6 or Toll-like receptor (TLR) agonists that are able to modify the expression of selectins, integrins, chemokines, and chemokine receptors. 7,8 Along this line, we recently reported that intravaginal (IVAG) administration of CpG (a TLR-9 agonist) resulted in the accumulation of CD8 T cells co-expressing CCR5 and CXCR3 chemokine receptors and E-selectin ligands (ESL), most probably through CpG-induced expression of CCL5, CXCL9, CXCL10, CXCL11, and/or E-selectin 9 . Most importantly, in a murine model of cervical cancer, this strategy resulted in more efficient genital tumor regression than vaccination alone.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4][5] An alternative approach, irrespective of the immunization route, is to enhance T-cell attraction to the tumor site through the local application of selected chemokines 6 or Toll-like receptor (TLR) agonists that are able to modify the expression of selectins, integrins, chemokines, and chemokine receptors. 7,8 Along this line, we recently reported that intravaginal (IVAG) administration of CpG (a TLR-9 agonist) resulted in the accumulation of CD8 T cells co-expressing CCR5 and CXCR3 chemokine receptors and E-selectin ligands (ESL), most probably through CpG-induced expression of CCL5, CXCL9, CXCL10, CXCL11, and/or E-selectin 9 . Most importantly, in a murine model of cervical cancer, this strategy resulted in more efficient genital tumor regression than vaccination alone.…”
Section: Introductionmentioning
confidence: 98%
“…8 The receptor repertoire includes numerous pattern recognition receptors (PRRs), which encompass most Toll-like receptors (TLRs), including TLR3 and TLR9. [9][10][11] In addition, MCs are reported to express complement receptors, G proteincoupled receptors, and CD48. This equipment enables MCs to recognize a wide array of exogenous ligands, pathogenassociated molecular patterns and endogenous ligands, all of which trigger danger signals in the host.…”
Section: Introductionmentioning
confidence: 99%
“…TLRs serve as sensors against pathogens that invade the host by recognizing pathogen-associated molecular patterns (Matsushima et al, 2004). Each TLR has been identified to recognize a distinct ligand, supported and confirmed by previous observation of TLR-knockout mice and specific gene modifications.…”
Section: Introductionmentioning
confidence: 76%
“…During HCMV infection, monocytes and their derivative cells, which represent the first line of defense, are thought to participate in innate immune response by restricting viral dissemination. Experimental studies indicate that recognition or binding of HCMV particles, which can take place either on the cell surface (Hampton et al, 1991;Peiser et al, 2002;Abate et al, 2004;DeWitte-Orr et al, 2010) or within intracellular endosome (Jiang et al, 2004;Matsushima et al, 2004;Jiang et al, 2009), is an early and potent regulatory signal for the activation of pro-inflammatory cytokines. Monocyte-derived cytokines are essential in triggering T-cell response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation